Exploration of Oxygen-Induced Retinopathy Model to Discover New Therapeutic Drug Targets in Retinopathies - Vähätupa, Maria; Järvinen, Tero A. H.; Uusitalo-Järvinen, Hannele (Frontiers in Pharmacology, 2020)
Oxygen-induced retinopathy (OIR) is a pure hypoxia-driven angiogenesis model and the most widely used model for ischemic retinopathies, such as retinopathy of prematurity (ROP), proliferative diabetic retinopathy (PDR), and retinal vein occlusion (RVO). OIR model has been used to test new potential anti-angiogenic factors for human diseases. We have recently performed the most comprehensive characterization of OIR by a relatively novel mass spectrometry (MS) technique, sequential window acquisition of all theoretical fragment ion mass spectra (SWATH-MS) proteomics and used genetically modified mice strains to identify novel molecular drug targets in angiogenic retinal diseases. We have confirmed the relevance of the identified molecular targets to human diseases by determining their expression pattern in neovascular membranes obtained from PDR and RVO patients. Based on our results, crystallins were the most prominent proteins induced by early hypoxic environment during the OIR, while actomyosin complex and Filamin A-R-Ras axis, that regulates vascular permeability of the angiogenic blood vessels, stood out at the peak of angiogenesis. Our results have revealed potential new therapeutic targets to address hypoxia-induced pathological angiogenesis and the associated vascular permeability in number of retinal diseases.